Informal Popular Housing and the Territorialization of State Policies for Urban Regularization in Comodoro Rivadavia (Chubut, Argentina) - Chanampa, Magali (2024)
The following article presents the most significant results and reflections that were part of the author’s PhD thesis in Geography. The central focus revolves around the informal popular housing and its problematization in the context of state policies and urban regularization and integration processes in Comodoro Rivadavia, Chubut, Argentina. Its approach through qualitative research strategies aimed to analyze the genesis of informal settlements, particularly emphasizing municipal policies designed for their regularization and urban integration. Within this framework, a critical analysis was taken into account regarding the territorialization of these processes to unveil the logics of compartmentalization and socio-spatial hierarchization that sustain and reproduce certain interventions of this nature within neighborhoods stemming from land seizures.